Strategi Pemasaran Corporate Event Dalam Membangun Customer Relation di PT. Visicita Imaji Semesta - Piero, Grandtino; Sumadi, I Gede; Asmarani, I Gusti Ayu Ratih (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Pariwisata Bali, 2025)
The event organizer industry continues to grow along with the increasing demand from companies to build long term relationships with clients through corporate event, PT. Visicita Imaji Semesta is an experienced event service provider that has handled numerous national scale projects. However, the company has faced a decline in repeat orders, affecting its business performance, therefore an appropriate marketing strategy is needed to strengthen customer relations. This study aims to analyze the corporate event marketing strategy implemented by PT. Visicita Imaji Semesta in building customer relationships, the research uses a descriptive qualitative method with data collected through intereviews, observation, and documentation. SWOT analysis is used to identify the internal and external factors, strengths, weaknesses, opportunities, and threats that influence that company’s marketing strategies. The finding indicate that the company applies SO strategies by integtrating creativity and open communication with digitas trends such as hybrid events, ST strategies are implemented by maintaining intensive communication and providing value added services to clients. WO strategies internal limitations through technology, while WT strategies focus on strengthening SOP, staff training, and quality control systems, there four strategies have proven effective in fostering client satisfaction, loyalty, and trust, forming the foundation of sustainable long term relationships.